276 SCRNA SEQUENCING OF SINGLE EAC ORGANOID REVEALS HETEROGENEITY OF STEM CELL LIKE POPULATIONS. (14th September 2020) - Derouet, M; Wilson, G; Darling, G; Yeung, J
Abstract:  : Tumor heterogeneity is one of the main contributor of poor response to treatment and metastasis. Esophageal adenocarcinoma (EAC) is known to be second only to melanoma in terms of heterogeneity. Robust in vitro models of EAC are lacking. In our patient derived organoid (PDO) culture, we identified different organoid morphologies from the same patient. We decided to investigate the transcriptional programs of the different organoid morphologies. Methods: EAC organoids were established from endoscopic biopsies from 4 different patients. Based on their morphology, individual organoids were isolated and dissociated into single cell suspensions. The 10X Genomics platform was used for single cell RNA sequencing. Results: The two morphologies identified by histology were cystic and intestinal. For the two intestinal populations the samples could be divided into stem-like (905/1646 and 1472/1926) and differentiated populations. Interestingly, we observed differences in the number of cycling cells in these Lgr5+ stem-like populations (905/905 and 337/1926). For the cystic samples the two populations could also be divided into stem-like populations (758/923 and 284/784) and differentiated populations. We also observed cell cycle differences in the Lgr5+ stem-like populations in these samples. RNA velocity analyses on each sample verified a differentiation trajectory from the stem-like to the differentiated cells. Conclusion: Studying EAC organoids provides us with the ability to profile the transcriptional programs of progenitor-like cells, which are difficult to isolate from gross tumor. We demonstrate that we can isolate individual organoids and study them at single-cell resolution to evaluate the different types of organoid generating cells based on their morphology.